Foodborne Illness Outbreaks: Surveillance and Prevention Strategies (International Journal of Food and Nutritional Sciences, 2021)
Foodborne illness outbreak prevention is complex and crucial to public health, requiring a diverse approach that includes food supply chain initiatives. This study compares HACCP, Regulatory Oversight, Education and Training, Surveillance Networks, Traceability Systems, Research and Innovation, Emergency Response Plans, and International Collaboration as prevention strategies. Food processing businesses benefit from HACCP's risk assessment and control techniques, which pinpoint important locations for preventive action. Food safety rules and regular inspections provide a legal foundation for food supply chain compliance. Education and training programs educate food handlers and the public, promoting safe food practices and informed decision-making. Integrated technologies and global collaboration enable real-time information exchange, early identification, and coordinated foodborne danger responses in surveillance networks. Transparent traceability systems allow prompt identification and removal of tainted products, protecting the food distribution network. Research and Innovation increase food safety by using technology and studying new hazards. When well-developed and tested, Emergency Response Plans provide quick and orderly outbreak responses. Finally, International Collaboration emphasizes cross-border collaboration, information sharing, and international norms due to foodborne risks' global character. These concepts create a flexible framework for food safety, outbreak prevention, and public health. Creating a resilient and responsive global food safety ecosystem requires constant innovation, education, legislation, and collaboration